2000
DOI: 10.1097/00006123-200009000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Headache after Supratentorial Craniotomy

Abstract: Although the incidence of persistent head pain after supratentorial craniotomy is lower than that reported for posterior fossa procedures, the incidence is not trivial. The cause of persistent pain deserves further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
31
0
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 14 publications
3
31
0
6
Order By: Relevance
“…Persistent headache following craniotomy [37] (in particular base of skull surgery) has long been recognised, and several studies [40–42] have highlighted its importance. There is, however, a paucity of data regarding persistent headache after supratentorial craniotomy [43]. Headache is most often described as tension type, with episodic acute exacerbations mimicking migraine.…”
Section: Incidence Of Chronic Pain After Craniotomymentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent headache following craniotomy [37] (in particular base of skull surgery) has long been recognised, and several studies [40–42] have highlighted its importance. There is, however, a paucity of data regarding persistent headache after supratentorial craniotomy [43]. Headache is most often described as tension type, with episodic acute exacerbations mimicking migraine.…”
Section: Incidence Of Chronic Pain After Craniotomymentioning
confidence: 99%
“…Kaur et al . [43] published a study of 145 patients who underwent anterior temporal lobectomies for intractable epilepsy over a 9‐year period. To eliminate confounding causes of headache, all patients studied were seizure‐free, none had progressive mass lesions or persisting vascular anomalies, and none had major complications of surgery.…”
Section: Incidence Of Chronic Pain After Craniotomymentioning
confidence: 99%
“…Gee et al, in a retrospective study, have reported a PCH incidence of 19% after craniotomies performed for treatment of several diseases such as brain tumours, epilepsy and intracranial haemorrhage (6). Kaur et al have reported an incidence of 17.5% of headaches that persisted for > 2 months and of 11.9% for > 1 year after temporal lobectomy for the treatment of epilepsy, considering only headaches with pain localized on the injury site, or headaches of a different type from those of the preoperative period (7).…”
Section: Introductionmentioning
confidence: 99%
“…Cefaleia crônica resultante de trauma craniano tem sido amplamente estudada [3][4][5] . A relação causa e efeito entre a lesão e a cefaleia é baseado no aparecimento da dor em um período imediatamente após o evento.…”
Section: Discussionunclassified